Effect of self-cementing properties on the resilient behaviour of recycled concrete aggregates used in base and subbase - Wang, Chong; Chazallon, Cyrille; Hornych, Pierre; Mouhoubi, Saïda; Jing, Peng (Road Materials and Pavement Design, 2024)
International audience The strength and stiffness of unbound pavement base and subbase layers built with recycled concrete aggregates (RCA) can increase due to the self-cementing properties of RCA. While the effect of different levels of self-cementing properties on resilient deformation behaviour has not been thoroughly studied. In this research, the self-cementing properties, microstructure and resilient deformation behaviour of two different RCA, NRCA (New RCA, crushed recently) and ORCA (Old RCA, crushed long time ago), showing significantly different levels of self-cementing properties, after curing for different times (1, 180, 360 and 720 days), were studied by calorimeter tests, mercury intrusion porosimetry (MIP) tests and repeated load triaxial tests (RLTT). The results indicate that long-term resilient behaviour is influenced by the level of self-cementing properties. For NRCA, showing strong self-cementing properties, the microstructure and resilient deformation behaviour were improved after curing for 720 days, which were comparable to those of lightly treated materials. On the contrary, for ORCA, showing negligible self-cementing properties, the resilient behaviour is not affected by curing.